The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.oraloncology.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

PRAME expression in head and neck cancer correlates with markers of poor prognosis and might help in selecting candidates for retinoid chemoprevention in pre-malignant lesions

Abstract: Objectives PRAME (Preferentially Expressed Antigen in Melanoma) is a tumor-associated antigen recognized by immunocytes, and it induces cytotoxic T cell-mediated responses in melanoma. PRAME expression in tumors interferes with retinoic acid receptor (RAR) signaling thus promoting tumor progression. Here, we study PRAME expression in head and neck squamous cell carcinoma (HNSCC) to determine its potential clinical significance. Materials and Methods PRAME expression in HNSCC was evaluated by immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…A low expression of PRAME correlated with a better 5-year OS probability, a finding similar to that observed in other cancers. (33,36,39,40) Moreover, the correlation between better OS and low PRAME expression was detected in patients belonging to SHH-and G3-MB subgroups, while a larger number of patients is needed to confirm this finding in WNT-and G4-MB subgroups. The statistically significant correlation between low PRAME expression and better OS probability was also maintained considering as cut-off for PRAME mRNA expression median value, as well as 1° and 3° quartiles.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A low expression of PRAME correlated with a better 5-year OS probability, a finding similar to that observed in other cancers. (33,36,39,40) Moreover, the correlation between better OS and low PRAME expression was detected in patients belonging to SHH-and G3-MB subgroups, while a larger number of patients is needed to confirm this finding in WNT-and G4-MB subgroups. The statistically significant correlation between low PRAME expression and better OS probability was also maintained considering as cut-off for PRAME mRNA expression median value, as well as 1° and 3° quartiles.…”
Section: Discussionmentioning
confidence: 88%
“…(29) Several authors reported PRAME expression in many cancers, but presently the biological and clinical meaning of this finding is not yet completely elucidated and, in some cases, the association between PRAME expression and disease prognosis is controversial. (30)(31)(32) In particular, in solid malignancies, including head and neck cancer, (33,34) liposarcoma,(35) uveal melanoma, (12,36) osteosarcoma, (37,38) breast cancer (39) and neuroblastoma (40) high PRAME expression correlates with advanced stage disease and poor clinical outcome, whereas in pediatric acute leukemia PRAME overexpression was found to predict good outcome. (41,42) Research.…”
Section: Discussionmentioning
confidence: 99%
“…Because exosomes are known to carry immunosuppressive as well as immuno-activating proteins (27), we selected and respectively blotted for several of these proteins, as shown in the blot horizontal sections A and B. Section C shows expression of TSG101 used as an exosome marker and of PRAME used here as a marker of exosomes potentially derived from the tumor (28). Figure 4A shows that the protein profiles are different for every subject.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies of HNSCC cell lines showed that PRAME protein and mRNA were overexpressed in tumor cells but not in normal keratinocytes (HaCaT cells) [15]. Also, PRAME silencing with siRNA in HNSCC cells followed by co incubation with clinically relevant concentrations of RA decreased in vitro migration of these cells and induced their apoptosis [S zczepanski MJ, L uczak M, W hiteside TL, U npublished D ata ].…”
Section: Prame As a Potential Prognostic Biomarker In Hnsccmentioning
confidence: 99%
“…Furthermore, PRAME was found to be overexpressed in HNSCC of patients with advanced disease (stages III and IV). In aggregate, these data suggested that elevated PRAME expression in HNSCC could potentially serve as a biomarker of poor outcome and as a future therapeutic target [15]. …”
Section: Prame As a Potential Prognostic Biomarker In Hnsccmentioning
confidence: 99%